Avaliação da atividade e mecanismo de ação antiúlcera do extrato hidroetanólico das folha de Fridericia chica (Bonpl.) L.G.Lohmann - Figueiredo, Fabiana de Freitas (2023)
Fridericia chica (Bonpl.) L.G. Lohmann (Bignoniaceae), is a vine native to Brazil, found in all Brazilian biomes. It is better known in Brazil as "carajiru", and home remedies made from the leaves have been used to cure disorders including stomach ulcers and other gastrointestinal disorders. The study aims to evaluate the antiulcer activity and mechanism of action of the hydroethanolic extract of Fridericia chica leaves (EHFc) in in vivo experimental models. The leaves of F. chica were macerated in a 70% hydroethanolic solution (1:10, p.v) to obtain the EHFc. The antiulcerogenic activity of cEHF was evaluated using models of acute gastric ulcer induced by acidified ethanol, indomethacin and chronic and water immersion stress induced by topical application of acetic acid in the serosal layer of the stomach of mice. Histological analysis and activities of myeloperoxidase (MPO) and malondialdehyde (MDA) and glutathione (GSH) levels, and the cytokines TNF-α, IL-1β and Il-10, were also evaluated in gastric tissues of acid-ulcerated animals. acetic. To elucidate possible mechanisms of antiulcerogenic action of EHFc, mucus production was determined using the alcian blue method. And the volume, free and total acidity of gastric secretion, in a pyloric ligation model. The role of PGs (indomethacin), NO (L-NAME) K+ATP channels (glibenclamide), α2- adrenoceptor (yohimbine) in gastric ulcer was evaluated. In models of acute gastric ulcers, pretreatment with EHFc (1, 5 and 20 mg/kg) reduced the ulcerated area by 64.41% (p<0.001), 54.23% (p<0.01) and 38. 71% (p<0.01), respectively. In the indomethacin experiment, there was no change in the doses tested, while in the stress ulcer due to immersion in water, there was a reduction in lesions at the doses of 1, 5 and 20 mg/kg by 80.34% (p<0.001%), 68 .46% (p<0.01) and 52.04% (p<0.01%). EHFc increased mucus production at doses of 1 and 20 mg/kg by 28.14% (p<0.05) and 38.35% (p<0.01), respectively. In the pyloric ligation-induced gastric ulcer model, EHFc decreased total acidity at all doses by 54.23%, 65.08%, and 44.40% (p<0.05), and gastric secretion volume by 38. 47% at the 1 mg/kg dose (p<0.05) and increased free acidity at the 5 mg/kg dose by 11.86% (p<0.05). Furthermore, EHFc involved increases in GSH activity and decreases in MPO activity and MDA levels. The chronic gastric ulcer model, EHFc (1, 5 and 20 mg/kg) significantly decreased the ulcerated area at all doses tested by 71, 37%, 91.00% and 93.46% (p<0.001), respectively. In the histological analysis, HEFc promoted the healing of gastric lesions by stimulating the formation of granulation tissue and, consequently, epithelialization. On the other hand, regarding the effect of HEFc on gastric emptying and intestinal transit, it was observed that the extract did not alter gastric emptying, but there was an increase in intestinal transit at the dose of 1mg/kg (p < 0.01). Thus, it can be concluded that the inhibition of neutrophils and the release of pro and anti-inflammatory mediators contributed to the anti-inflammatory activity of EHFc. It can also be stated with these results that Fridericia chica leaves result in the prevention and protection of gastric ulcer.